1998
DOI: 10.1063/1.367022
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic determination of non-radiative carrier lifetimes

Abstract: From photoacoustic (PA) experiments we determine the nonradiative carrier lifetime in direct band-gap semiconductors. We use the Rosencwaig and Gerscho model to calculate the PA signal in semiconductors taking into account the distinction between non-radiative and radiative carrier lifetimes. We have assumed that for our high quality crystalline samples, the main contribution to the non-radiative processes comes from CHCC and CHSH Auger recombination for n and p-type materials, respectively. For GaAs, InSb and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 20 publications
1
29
0
1
Order By: Relevance
“…The plasma wave effect observed for CdTe/glass system was reported by Bernal-Alvarado et al [5]. The influence of the plasma wave effect on a photoacoustic signal of a polycrystal CdTe/glass system was also investigated by Martin et al [6].…”
mentioning
confidence: 83%
“…The plasma wave effect observed for CdTe/glass system was reported by Bernal-Alvarado et al [5]. The influence of the plasma wave effect on a photoacoustic signal of a polycrystal CdTe/glass system was also investigated by Martin et al [6].…”
mentioning
confidence: 83%
“…19 Note also that in many OPC studies involving a variety of semiconductors, more complex phase behavior with a minimum in the phase plot is reported. [9][10][11][12][13][14][15][16][17] This nonlinear behavior of the phase data is attributed to surface and bulk recombination processes of photogenerated carriers in those materials. However, our observation indicates that for this sample, the photogenerated excess carrier recombination processes do not contribute to the PA signal in any significant manner in the frequency range of our investigations.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…The Dramicanin model is very useful for the analysis of PA signal amplitude and phase at the front and rear surfaces of semiconductor samples. Subsequently, in more recent years, using PA phase measurements in the heat transmission configuration, carrier transport properties such as carrier diffusion coefficient, carrier recombination velocity, and mean recombination time were evaluated together with the thermal diffusivity of a large number of semiconducting samples, [9][10][11][12][13][14][15][16][17] namely, GaAs, CdTe, Si solar cells, CdInGaS 4 , InSb, GaSb, etc.…”
Section: Introductionmentioning
confidence: 99%
“…By using these values in the expression for the thermal conductivity K = ρC p α a value of α = 0.154 cm 2 /s is obtained. Marin et al [35] reported the thermal diffusivity value of 0.24 cm 2 /s for the GaSb compound. Since the thicknesses of our samples are 520 and 500 m, the chopping frequency was varied from 10 to 270 Hz in order to achieve the thermally thick condition.…”
Section: Opc Photoacoustic Measurementsmentioning
confidence: 98%